"Emotional intelligence, job satisfaction and perceived workers’ productivity in selected workplace organizations: empirical evidence from Nigeria " (2014)
Emotions of employees play a significant role in an organization's life. The resultant effect of emotional intelligence on employees' job satisfaction is critical to the success of the organization. Inability of managers or employees to regulate their emotions and manage others' emotions can result into conflicts and occupational stress with adverse effect on productivity. This study investigated the impact of emotional intelligence and job satisfaction on employees' productivity at workplace. The descriptive survey research design of the ex-post-facto type was used for the study. The study population consists of all the workers of selected manufacturing and hospitality industries in Ibadan Metropolis. A total of 235 employees consisting of 147 male and 88 female whose ages ranged between 2l and 57 with mean of 30.3 years and a standard deviation of 5.4 were used for the study. Questionnaire tagged “Emotional Intelligence, Job Satisfaction and Workers' Productivity Questionnaire (EIJSWPQ)” with four sub-sections was used to collect data. Emotional intelligence was measured through a scale consisting twenty items. Job satisfaction scale consist 10 items. Employee productivity was measured using 10-item scale. Multiple Regression Analysis was used to analysis the two research hypotheses raised for the study. The result revealed that the joint effect of emotional intelligence and job satisfaction on employees' productivity was significant. It was also established that emotional intelligence and job satisfaction had a significant contributive effects on employee productivity. It was recommended that industrial social workers in conjunction with the human resource managers in the workplace should organise regular training on emotional intelligence for all categories of employees to enhance their job performance and increase their productivity.